Comparative Proteomics and Secretomics Revealed Virulence and Antibiotic Resistance-Associated Factors in Vibrio parahaemolyticus Recovered From Commonly Consumed Aquatic Products - Zhu, Zhuoying; Yang, Lianzhi; Yu, Pan; Wang, Yongjie; Peng, Xu; Chen, Lanming (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is a gram-negative seafoodborne bacterium and can cause severe human gastroenteritis and septicemia diseases and even death. The bacterium of environmental origins lacking major virulence genes (tdh and trh) is associated with infectious diarrhea disease in humans. The emergence of multidrug-resistant V. parahaemolyticus increases the difficulty and cost of clinical treatment. Identification of risk factors in V. parahaemolyticus is imperative for assuming food safety. In this study, we obtained secretomic and proteomic profiles of V. parahaemolyticus isolated from twelve species of commonly consumed aquatic products, and identified candidate protein spots by using two-dimensional gel electrophoresis (2-DE) and liquid chromatography tandem mass spectrometry (LC-MS/MS) techniques. Total 11 common and 28 differential extracellular proteins were found from distinct secretomic profiles, including eight virulence-associated proteins: outer membrane channel TolC, maltoporin, elongation factor Tu (EF-Tu), enolase, transaldolase, flagellin C, polar flagellin B/D and superoxide dismutase, as well as five antimicrobial and or heavy metal resistance-associated ABC transporter proteins. Comparison of proteomic profiles derived from the twelve V. parahaemolyticus isolates also revealed five intracellular virulence-related proteins, including aldehyde-alcohol dehydrogenase (AdhE), outer membrane protein A (OmpA), alkyl hydroperoxide reductase C (AhpC), phosphoenolpyruvate-protein phosphotransferase (PtsA) and phosphoglycerate kinase (PGK). Additionally, our data indicated that aquatic product matrices significantly altered proteomic profiles of the V. parahaemolyticus isolates with a number of differentially expressed proteins identified. The results in this study meet the increasing need for novel diagnosis candidates of the leading seafoodborne pathogen worldwide.